2011
DOI: 10.1111/j.1751-7176.2011.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium Levels and Hypertension Among US Adults

Abstract: Serum calcium levels have been shown to be associated with cardiovascular disease (CVD); however, it is not clear whether serum calcium levels are related to hypertension, a risk factor for CVD. The authors examined the association between serum calcium and hypertension in a representative sample of US adults. A cross-sectional study of 12,405 third National Health and Nutrition Examination Survey participants 20 years and older was conducted. Serum total and ionized calcium levels were analyzed as quartiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 29 publications
6
34
2
Order By: Relevance
“…Our results show that serum calcium was higher in cases than in controls. Sabanayagam and Shankar15 reported that higher serum calcium levels were positively correlated with hypertension in a representative sample of US adults, which is consistent with our findings. Further, Cook et al have shown that myeloperoxidase-mediated modulation of intracellular calcium ion levels may exacerbate endothelial dysfunction, a key early event in hypertension 16.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that serum calcium was higher in cases than in controls. Sabanayagam and Shankar15 reported that higher serum calcium levels were positively correlated with hypertension in a representative sample of US adults, which is consistent with our findings. Further, Cook et al have shown that myeloperoxidase-mediated modulation of intracellular calcium ion levels may exacerbate endothelial dysfunction, a key early event in hypertension 16.…”
Section: Discussionsupporting
confidence: 92%
“…The findings revealed that there was significant reduction in albumin concentration of test group B (hypertensive patients with cataract) with Mean ± SD = 44.35 ± 11.99 g/L when compared to the Mean ± SD = 48.12 ± 8.20 g/L of the control samples and this indicates that hypertension (with cataract) had significantly decreased levels of plasma albumin when compared to non-cataract hypertensive patients. This finding is similar to work done by Kayode et al, [9] which revealed significant reduction in plasma albumin concentration level in cataract patients and also in line with the results reported by Sabanayagam et al [10], which state that, people with severe hypertension have a higher risk of cataract than those with mild hypertension. Several studies indicated a linear positive correlation between blood pressure and cataract risk [11; 12] and the duration of hypertension is also an important factor, indicating a relationship between longer duration and increased cataract risk [13].…”
Section: Resultssupporting
confidence: 82%
“…Similarly, In a previous study Lind et al 9 found that subjects with a history of MI have significantly higher serum calcium than those without infarction. Our finding of a positive association between elevated serum calcium level and AMI is also consistent with other studies 8,15 . Herrmann et al 16 demonstrated that increased serum calcium predisposes calcific deposition in the valve cusps and coronary arteries, which could cause significant aortic valve stenosis and accelerate coronary atherosclerosis; this can mismatch the myocardial oxygen supply and demand.…”
Section: Discussionsupporting
confidence: 82%